Engineering lattice metamaterials for extreme property, programmability, and multifunctionality - Jia, Zian; Liu, Fan; Jiang, Xihang; Wang, Lifeng (Journal of applied physics, 2020)
Making materials lightweight while attaining a desirable combination of mechanical, thermal, and other physical properties is the “holy grail” of material science. Lattice materials, because of their porous structures and well-defined unit cell geometries, are suitable candidates to achieve lightweight with precisely tailored material properties. Aided by additive manufacturing techniques, a variety of lattice metamaterials with exceptional and unusual properties have been fabricated recently, yet, the rational designs of lattice metamaterials with programmability and multifunctionality are still challenging topics. In this perspective, we identify three emerging directions for lattice metamaterials: (1) developing architected lattice metamaterials with extreme and unusual properties that are non-typical in bulk materials, (2) designing lattice metamaterials with programmable mechanical properties that respond differently at different environments, loading paths, or controls, and (3) exploiting lattice metamaterials with multifunction, including tailorable thermal, mechanical, optical, piezoelectric, and negative-index material properties. These emergent directions portend the transitioning of lattice metamaterials from the stage of conventional materials to smart, adaptive, and versatile materials, which provide solutions to realistic problems in transport systems, wearable devices, and robotics, and continue to push the boundary of possibilities of architected metamaterials.